Second year of COVID-19 pandemic: mental health among Indonesian urban population - Hardi, Nicholas; Gracia, Isadora; Hananta, Linawati (Intelektual Pustaka Media Utama, 2023)
Mental health problems, particularly anxiety and depression, have increased since the early pandemic. This phenomenon still occurs when the pandemic reached its second year. The study explored the prevalence of anxiety and depression among the urban population. A cross-sectional study was conducted during Jakarta's third dose of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination programs. The Indonesian version of generalized anxiety disorder-7 (GAD-7) and the patient health questionnaire-9 (PHQ-9) were used to estimate clinically significant anxiety and depression, respectively. Out of the 356 participants, 18.5% and 29.2% of participants presented clinically significant anxiety and depression, respectively. Age differences between the probable anxiety and depression groups with their respective counterparts were statistically significant (p<0.001). Both groups showed a lower mean age. Lower age showed significantly higher anxiety (OR 1.05; 95% CI 1.0-1.1) and depressive problems (OR 1.07; 95% CI 1.0-1.1). Our result indicated that clinically significant anxiety and depression symptoms were prevalent among the urban population during the second year of the pandemic. Age differences might be an important predictive factor for both symptoms. Age-specific interventions are considered helpful to achieve better mental health and reduce the prevalence.